Analysis of the injuries and workload evolution using the RPE and s-RPE method in basketball - Laura Garcia; Antoni Planas; Xavier Peirau (Elsevier, 2022)
The quantification of training loads provides valuable information to reduce overtraining and detecting the risk of injury. The present study looks into the evolution of the training load using the RPE and s-RPE method and describes the injuries observed. It is an observational study based on 9 subjects of the Pardinyes basketball team (Leb Plata category) who, in each practice and match, recorded their RPE. This value, together with the volume (in minutes), provides the s-RPE. All injuries and their typology were also recorded during the first round of the competition. A total of 124 sessions were registered and 14 injuries were described in the period that went from 09/19/2019 to 02/15/2020. The load evolution of each player has been compared to the team average and to the one perceived by the coach. The lower extremity was, by far, the most injured one (13/14 injury events). The highest percentage of injuries was registered during the last part of the training sessions and matches, coinciding with the highest physical and psychological fatigue, and 64% of them were due to microtrauma. These inexpensive and easy-to-use methods (RPE and s-RPE) provide valuable data for planning, in order to adjust loads and prevent overtraining and injuries. It is necessary to manage workload to provide the player with the ideal stimulus, minimizing the risk of injury and, at the same time, maximizing their performance.